2008
DOI: 10.3800/pbr.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the planktonic food web off Cape Esan, southwestern Hokkaido, Japan

Abstract: Abstract:The planktonic food web structure in the water off Cape Esan, southwestern Hokkaido, Japan was investigated at approximately one or two-month intervals from May 1997 through June 1999, based on biomass data of pico-(0.2-2 mm), nano-(2-10 mm), micro-(10-200 mm) and mesoplankton (200-20,000 mm). In spring (March-April), the water column was stratified and a spring diatom bloom occurred. In addition, microzooplankton and copepod biomass was high among the heterotrophic plankton in spring. In other season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The ANP biomass obtained in the present study is comparable to that found off Cape Esan near Funka Bay (<5->40 µg C L −1 , Shinada et al 2008), which is lower than at the same site in Sagami Bay in 2003-2005 (1.14-191.77 µg C L −1 , Ara & Hiromi 2009), and is higher than in Funka Bay (2-10 µm: 0.57-7.88 µg C L −1 , Odate et al 1993). Ph-C M obtained in the present study is comparable to that found in the Oyashio region off Akkeshi (2.5-410.7 µg C L −1 , Shinada et al 2001) and off Cape Esan near Funka Bay (<10->300 µg C L −1 , Shinada et al 2008), and is higher than in Funka Bay (>10 µm: 0.90-193.01 µg C L −1 , Odate et al 1993). The total Ph-C obtained in the present study is comparable to that found in the Oyashio region off Akkeshi (8-418 µg C L −1 , Shinada et al 2001), which is lower than in Tokyo Bay (mean±SD: 392.7±300.5 µg C L −1 , Furuya & Marumo 1983), and is higher than that in and near Funka Bay (3.3-245.2 µg C L −1 , Odate et al 1993, Shinada et al 2005 (Table 3).…”
Section: Phytoplankton Biomass and The Ph-c/chl-a Ratiosupporting
confidence: 84%
See 2 more Smart Citations
“…The ANP biomass obtained in the present study is comparable to that found off Cape Esan near Funka Bay (<5->40 µg C L −1 , Shinada et al 2008), which is lower than at the same site in Sagami Bay in 2003-2005 (1.14-191.77 µg C L −1 , Ara & Hiromi 2009), and is higher than in Funka Bay (2-10 µm: 0.57-7.88 µg C L −1 , Odate et al 1993). Ph-C M obtained in the present study is comparable to that found in the Oyashio region off Akkeshi (2.5-410.7 µg C L −1 , Shinada et al 2001) and off Cape Esan near Funka Bay (<10->300 µg C L −1 , Shinada et al 2008), and is higher than in Funka Bay (>10 µm: 0.90-193.01 µg C L −1 , Odate et al 1993). The total Ph-C obtained in the present study is comparable to that found in the Oyashio region off Akkeshi (8-418 µg C L −1 , Shinada et al 2001), which is lower than in Tokyo Bay (mean±SD: 392.7±300.5 µg C L −1 , Furuya & Marumo 1983), and is higher than that in and near Funka Bay (3.3-245.2 µg C L −1 , Odate et al 1993, Shinada et al 2005 (Table 3).…”
Section: Phytoplankton Biomass and The Ph-c/chl-a Ratiosupporting
confidence: 84%
“…The cyanobacterial biomass obtained in the present study is comparable to that found in other bays and coastal waters in Japan, e.g. at the same site in 2003-2005, off Manazuru in Sagami Bay and in Oginohara Bay (Ishinomaki Bay) (0.03-34.21 µg C L −1 , Hamasaki et al 1999, Ara & Hiromi 2009, Kamiyama et al 2009, and is lower than in and near Funka Bay (pico-phytoplankton: 0.61-80.3 µg C L −1 , Odate et al 1993, Shinada et al 2008 (Table 3). The ANP biomass obtained in the present study is comparable to that found off Cape Esan near Funka Bay (<5->40 µg C L −1 , Shinada et al 2008), which is lower than at the same site in Sagami Bay in 2003-2005 (1.14-191.77 µg C L −1 , Ara & Hiromi 2009), and is higher than in Funka Bay (2-10 µm: 0.57-7.88 µg C L −1 , Odate et al 1993).…”
Section: Phytoplankton Biomass and The Ph-c/chl-a Ratiomentioning
confidence: 74%
See 1 more Smart Citation
“…In particular, they might be inferred to reflect biomass during April–June, given that this interval corresponded to the time of highest biomass during two years of field observations near our core site E16 (Fig. 1; Shinada et al, 2008). Thus, the close correlation between the MARs of SCEs and Chl- a over the last two millennia indicates that long-term variations in zooplankton productivity from spring to early summer were controlled by spring phytoplankton productivity in this area.…”
Section: Discussionmentioning
confidence: 91%
“…The classical food web is a simple and direct pathway that transfers organic matter from large phytoplankton, such as diatoms and dinoflagellates, to metazoans (Miller & Wheeler, ). This food web often predominates in coastal waters where upwelling and advection drive high nutrient input (e.g., Ara & Hiromi, ; Shinada, Ban, & Ikeda, ). Since this pathway transfers phytoplankton production directly to metazoans, it delivers a large proportion of production to higher trophic levels.…”
Section: Introductionmentioning
confidence: 99%